Men undergoing medical circumcision at a community health centre: Knowledge and attitudes - Charles K. Baloyi; John V. Ndimande; Cila D. Kabongo; Jean Louis M. Yoko; Beya Mpinda (South African Family Practice)
Background: Human immunodeficiency viruses (HIV) and/or acquired immunodeficiency syndrome remains a significant global health issue, affecting millions of individuals worldwide. Medical male circumcision (MMC) demonstrated effectiveness in decreasing the spread of HIV, more specifically through heterosexual contact with HIV-positive partners. Studies have shown a correlation between male circumcision and lower HIV prevalence, especially in regions where circumcision is a cultural practice. The purpose of the study was to determine the knowledge and attitudes of men utilising the MMC services regarding circumcision.